2013
DOI: 10.1186/1471-2148-13-269
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of amplified fragment length polymorphisms (AFLP) indicate rapid radiation of Diospyros species (Ebenaceae) endemic to New Caledonia

Abstract: BackgroundRadiation in some plant groups has occurred on islands and due to the characteristic rapid pace of phenotypic evolution, standard molecular markers often provide insufficient variation for phylogenetic reconstruction. To resolve relationships within a clade of 21 closely related New Caledonian Diospyros species and evaluate species boundaries we analysed genome-wide DNA variation via amplified fragment length polymorphisms (AFLP).ResultsA neighbour-joining (NJ) dendrogram based on Dice distances show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…The present study, using ITS sequences and an extended list of species, suggests monophyly of the Lasiocephalus ‐ Culcitium species group but with neither of the two former genera monophyletic. Although relationships within the group are only partly resolved in both the ITS and AFLP datasets, suggesting a recent diversification (Turner et al., ), there is a partial congruence between the two markers, as AFLP cluster C corresponds to the ITS “páramo clade” (except for Senecio nivalis ) and AFLP clusters A and B correspond to the ITS “forest clade” (except for S. puracensis ) (Figure , Table ); incongruences will be discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study, using ITS sequences and an extended list of species, suggests monophyly of the Lasiocephalus ‐ Culcitium species group but with neither of the two former genera monophyletic. Although relationships within the group are only partly resolved in both the ITS and AFLP datasets, suggesting a recent diversification (Turner et al., ), there is a partial congruence between the two markers, as AFLP cluster C corresponds to the ITS “páramo clade” (except for Senecio nivalis ) and AFLP clusters A and B correspond to the ITS “forest clade” (except for S. puracensis ) (Figure , Table ); incongruences will be discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Although relationships within the group are only partly resolved in both the ITS and AFLP datasets, suggesting a recent diversification (Turner et al, 2013), there is a partial congruence between the two markers, as AFLP cluster C corresponds to the ITS "páramo clade" (except for Senecio nivalis) and AFLP clusters A and B correspond to the ITS "forest clade" (except for S. puracensis) ( Figure 6, Table 1); incongruences will be discussed below.…”
Section: Lasiocephalus-culcitium Species Groupmentioning
confidence: 99%
“…For H. deplanchei, H. subobtusum and H. leratii, other possible source areas are Southeast Asia, Australia and other Pacific Islands. Whereas LDD from Australia to NC has been shown in several groups (see references in Introduction), cases of LDD from Southeast Asia and NZ to NC are less common (but for Southeast Asia see studies on Piper L., Piperaceae; and Diospyros L., Ebenaceae;Turner & al., 2013). However, a key role of NZ in the origin of the NC flora was suggested by Pole (2010) based on the presence, in the NZ fossil record, of lineages that are now restricted to NC.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting the presence of cryptic species has implications for classification, conservation and biogeography. In New Caledonia, only two cases of cryptic flowering plant species have been revealed, in Spiraeanthemum A.Gray (Cunoniaceae; Pillon et al ., ) and Diospyros L. (Ebenaceae; Turner et al ., ). However, based on unpublished molecular data, Swenson & Munzinger () indicated that cryptic species might be present in Pycnandra .…”
Section: Introductionmentioning
confidence: 97%